POTENSI PSIKOLOGIS DALAM MENDIDIK SANTRI MENURUT AL-GAZA>LI - Khasan Ubaidillah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
As the children learning practices in the national learning system do not consider physical and spiritual dimensions, it can not lead to a humanist learning system, even it may be said as un-Islamic. Is Gaza>li>, a classical Islamic education leaders who offer the concept of human potential that can sinergize the two-dimensional requirements of human. Based on this, this article intends to study and applying the concepts of learning students. By using a descriptive analysis of the literature owned by Gaza>li> it is found that human potential consists of the potential birth (al-hiss al-khams) and the inner potential (al-khaya>l, at-tafakkur, al-khifz, at-taz|akkur dan al Musytarak). According to him, these two potentials have their different functions each of which greatly affect the learning process of students. Furthermore, the thesis Gaza>li> This was the same even able to integrate the theories of modern cognitive psychology and behavioral education.",